Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(a+b\right)-\left(a-b\right).\\ =a+b-a+b.\\ =2b.\\ \left(xy+yz-x\right)+\left(x+xy-2yz\right).\\ =xy+yz-x+x+xy-2yz.\\ =2xy-yz.\\ =\left(2m+7n-9mn\right)-\left(6mn+15m-27n-21\right).\\ =2m+7n-9mn-6mn-15m+27n+21.\\ =-13m+34n-15mn+21.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(2m+7n-9mn\right)-\left(6mn+15m-27n-21\right).\\ =2m+7n-9mn-6mn-15m+27n+21.\\ =-15mn-13m+34n+21.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2x2yz + 4xy2z - 5x2yz + xy2z - xyz
= (2x2yz-5x2yz)+(4xy2z+xy2z)-xyz
= -3x2yz + 5xy2z - xyz
b) x3-5xy+3x3+xy-x2+\(\dfrac{1}{2}\)xy-x2
= (x3+3x3)+(xy-5xy+\(\dfrac{1}{2}\)xy)-(x2+x2)
= 4x3-\(\dfrac{7}{2}\)xy-2x2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{xy}{2}=\frac{yz}{4,5}=\frac{xz}{8}=\frac{xy+yz+xz}{2+4,5+8}=\frac{29}{14,5}=2\)
\(\Rightarrow xy=4,yz=9,xz=16\)
\(\Rightarrow\left(xy\right).\left(yz\right).\left(xz\right)=4.9.16\)
\(\Rightarrow\left(xyz\right)^2=2^2.3^2.4^2\Rightarrow\left(xyz\right)^2=24^2\Rightarrow\orbr{\begin{cases}xyz=24\\xyz=-24\end{cases}}\)
Nếu xyz = 24 thì \(\hept{\begin{cases}x=\left(xyz\right):\left(yz\right)=24:9=\frac{8}{3}\\y=\left(xyz\right):\left(xz\right)=24:16=\frac{3}{2}\\z=\left(xyz\right):\left(xy\right)=24:4=6\end{cases}}\)
Nếu xyz = -24 thì \(\hept{\begin{cases}x=\left(xyz\right):\left(xz\right)=-24:9=-\frac{8}{3}\\y=-24:16=-\frac{3}{2}\\z=-24:4=-6\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
\(A=x^2yz=x.x.y.z=x.xyz\left(1\right)\)
\(B=xy^2z=x.y.y.z=y.xyz\left(2\right)\)
\(C=xyz^2=x.y.z.z=z.xyz\left(3\right)\)
Lấy (1)+(2)+(3),vế theo vế ta được:
\(A+B+C=x.xyz+y.xyz+z.xyz=\left(x+y+z\right).xyz=xyz\) (vì x+y+z=1)
Vậy A+B+C=xyz (đpcm)
![](https://rs.olm.vn/images/avt/0.png?1311)
a.
\(\left(xy\right).\left(yz\right).\left(xz\right)=3.6.18\\ \Rightarrow\left(x.y.z\right)^2=324\\ \Rightarrow\left[{}\begin{matrix}x.y.z=18\\x.y.z=-18\end{matrix}\right.\)
Nếu x.y.z=18
\(\Rightarrow\left[{}\begin{matrix}z=\left(xyz\right):\left(xy\right)=18:3=6\\x=\left(xyz\right):\left(yz\right)=18:6=3\\y=\left(xyz\right):\left(xz\right)=18:18=1\end{matrix}\right.\)
Nếu x.y.z = -18
\(\Rightarrow\left\{{}\begin{matrix}z=-6\\x=-3\\y=-1\end{matrix}\right.\)
Vậy...
a)Ta có:xy.yz.xz=3.6.18
x^2.y^2.z^2=324
(x.y.z)^2=18^2
x.y.z=18
Do đó:x=18:6=3
y=18:18=1
z=18:3=6
b)Ta có:xy.yz.xz=1.8.18
x^2.y^2.z62=144
(x.y.z)^2=12^2
x.y.z=12
Do đó:x=12:8=1,5
y=12:18=2/3
z=12:1=12
a: =a+b-a+b=2a
b: =xy+yz-x+x+xy-2yz=-yz
c: =2m+7n-9mn-6mn-15m+27n+21
=-13m+34n-15mn+21